2014
DOI: 10.1007/s10494-014-9564-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Dynamic Response of Swirling Flows Based on LES and Experiments

Abstract: The dynamic response of a swirling flow undergoing vortex breakdown is investigated via Large Eddy Simulation (LES) and experiments in a water flow facility. The investigation is carried out following previous work on the link between thermoacoustic combustion instabilities and coherent structures in lean premixed gas turbine combustors. The velocity field transfer function is obtained in LES from the Unit Impulse Response determined via application of a low intensity broadband noise perturbation of the inflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…An identification scheme employing a Wiener filter was proposed [12], which can use a single large-eddy simulation (LES) to determine the flame response. This method has been already used in the FTF calculations for axial swirlers [13] and conical swirlers in industrial burners [14,15], and the numerical results have been demonstrated to be in agreement with the experimental results [16]. Nevertheless, more efforts should made to open the black box of the FTF in order to understand the root cause of the HRR's high gain.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…An identification scheme employing a Wiener filter was proposed [12], which can use a single large-eddy simulation (LES) to determine the flame response. This method has been already used in the FTF calculations for axial swirlers [13] and conical swirlers in industrial burners [14,15], and the numerical results have been demonstrated to be in agreement with the experimental results [16]. Nevertheless, more efforts should made to open the black box of the FTF in order to understand the root cause of the HRR's high gain.…”
Section: Introductionmentioning
confidence: 92%
“…Researchers observed periodic fluctuations in the reaction zone and obtained the dominant frequency by POD [17]. In addition, swirling flames have been analyzed as the correlation between the POD modes and reprehensive fields [14][15][16][17][18]. The POD remedies the deficiency of the pattern in the FTF.…”
Section: Introductionmentioning
confidence: 99%
“…This further confirms that the system oscillation characteristic is determined by the effects on each side and their cooperation. The opposite phase between P 1 and P 4 is attributed to an additional half wave formed within the longer premixed chamber [18]. The oscillation mechanism of these two cases was further investigated by analyzing the corresponding LP/λP and the sound pressure oscillation phase at each measurement The oscillation mechanism of these two cases was further investigated by analyzing the corresponding LP/λP and the sound pressure oscillation phase at each measurement…”
Section: Setai Behavior Under Asymmetric Supply Structurementioning
confidence: 99%
“…SETAI behavior has been proven to be affected by the equipment's structure and operation parameters, which provided the chance for SETAI control, but conflicting results have been observed with regard to the effect of the heat output [9][10][11], equivalent ratio (ϕ) [12][13][14], and system structure [15][16][17][18]. Due to insufficient knowledge, SETAI control is generally achieved via empirical or semi-empirical methods, mainly classified into two kinds of approaches.…”
Section: Introductionmentioning
confidence: 99%